ʺThe content of professional development for teachers in schools in Canada in the context of educational informatizationʺ - Koliesnikov, R. (Problems of Engineer-Pedagogical Education, 2024)
The skills and competencies of a modern teacher are crucial in an era of rapid technological advancement and the information age. In Canada, one of the leading countries in education, the professional development of teachers holds significant importance, especially in the context of educational digitization. The substantive content of this process is defined by several key aspects. Firstly, one important aspect is access to current technologies and resources. Participants in professional development processes should have the opportunity to familiarize themselves with innovative teaching tools and develop their own digital skills. Secondly, the role of effective mentoring and support for colleagues in the context of educational digitization becomes particularly significant. Participants in professional development have the opportunity to receive assistance from experienced colleagues who help in the implementation of new technologies and pedagogical approaches into the teaching process. Thirdly, continuous self-educational and professional growth is a vital component. Teachers must be prepared for continuous improvement of their skills and knowledge in the field of information technologies and their integration into the educational process. Furthermore, the substantive content of professional development for teachers in Canadian schools in the context of educational digitization also includes studying pedagogical techniques that promote the development of digital literacy among students, as well as adapting educational programs to meet modern requirements and trends in the field of education. The substantive content of professional development for teachers in Canadian schools in the context of educational digitization plays an important role in shaping a qualified teaching corps capable of effectively implementing innovative technologies in the teaching process and contributing to the successful development of students in the digital world. According to research and statistics, educational digitization in Canada is constantly intensifying, which requires the presence of up-to-date knowledge and skills among educators. In this context, professional development programs for school teachers take into account not only substantive aspects but also the latest technologies that help improve the quality of teaching and upbringing.